Lysine-specific demethylase 1 regulates hematopoietic stem cell expansion and myeloid cell differentiation - Staehle, Hans Felix; Koellerer, Christoph; Staehle, Anne Marie; Schulze, Jana; Eble, Philipp; Müller, Anja; Zell, Franziska; Müller, Judith M.; Perner, Florian; Attia, Aya; Mallm, Jan-Philipp; Pozdnyakova, Olga; et al. (Cell death & disease, 2025)
The lysine-specific demethylase 1 (LSD1) regulates hematopoietic stem cell differentiation and has been identified as a therapeutic target in hematological disorders. LSD1 demethylates mono and dimethylated histones 3 at lysine 4 and 9. In addition, it acts as a scaffold for the formation of chromatin-modifying complexes that regulates the transcription of myeloid-lineage-specific genes in complex with GFI1, a transcriptional repressor. While both enzymatic and non-enzymatic functions of LSD1 have been well defined, the relative importance of these two functions in hematopoiesis remains incompletely understood. Here, we investigated the contribution of enzymatic and non-enzymatic functions of LSD1 to myelopoiesis. We show that myeloid differentiation is independent of the enzymatic functions of LSD1 but requires the non-enzymatic, scaffolding function, which directs GFI1 binding to target sequences. In the absence of the LSD1 protein, GFI1 DNA binding is diminished, and myeloid cell differentiation arrests at an immature, myelomonocytic-like cell stage, which overexpresses Prtn3. We provide functional data implicating Prtn3 as an effector of the stem cell expansion and myeloid maturation block caused by the loss of LSD1.